In What Ways We Depend: Academic Dependency Theory and the Development of East Asian Sociology. Issue 1 (16th March 2022) - Lee, Chengpang; Chen, Ying
Abstract: Since it was framed 20 years ago, Syed Farid Alatas's theory of academic dependence has made a long‐lasting impact within the global social science field, and has elevated the previous discussion on academic dependence. In this essay, we critically examine his theory of academic dependence with an original dataset that contains 22 top sociology institutions in East Asia, including China, Japan, South Korea, Singapore, Hong Kong, and Taiwan. We further engage the data, and theory within the global higher education ranking system, a theme that had not yet emerged when he framed his theory of academic dependence. Our findings suggest that (1) higher rankings do not create job opportunities for locally trained PhDs; (2) emphasis on the number of publications is still prevalent; (3) adopting the standards set up by the ranking agency re‐enforces the existing global division of academic labor. Overall, sociology in these societies after 20 years is now more dependent, rather than autonomous from, the Western academic center.